Importance of Odor from Forensic Perspective - Mutlu, Emre; Aşıcıoğlu, Faruk (The Bulletin of Legal Medicine, 2019)
As the detection of the odor of drugs, explosives or volatile organic compounds released by the human body may indicate the presence of smuggling, terrorism, living or dead individuals, it is of increasing importance in criminal investigations as it can associate a person with a particular place or an object. Although the tools and equipment used in scent detection have improved significantly in recent years and they have come close to competing with dogs which are biological detectors, dogs are considered to be the first choice for the detection of scent source due to their speed, versatility, ability to follow odor and their distinguishing features. In addition to advances in the detection of volatile organic compounds, the development of standardized applications for devices and dogs continuously increases the reliability of scent as evidence. The development of good practice guidelines will make it possible to use the methodology for pursuit and apprehension as an acceptable forensic evidence in criminal proceedings with increasing sensitivity, selectivity and reliability in detecting volatile organic compounds of interest. In this study, the anatomical, physiological and genetic differences of dogs, anatomical structures that play a role in scent detection, the main actors that are still used in this process with their histological and physiological mechanism, their relations with their trainers and trainers, their limitations, the basic principles and capacities of the analytical instruments used in this field and the progress made were investigated and intended to be presented to the reader in a well organized structure.